Virtual Heart Models Help Elucidate the Role of Border Zone in Sustained Monomorphic Ventricular Tachycardia - Castaneda Gavina, Eduardo; Suzuki, Masahito; Ashikaga, Hiroshi; Lluch, Èric; Meister, Felix; Mihalef, Viorel; Audigier, Chloé; Maier, Andreas; Halperin, Henry; Passerini, Tiziano (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2023)
Post-ischemic Ventricular Tachycardia (VT) is sustained by a depolarization wave re-entry through channel-like structures within the post-ischemic scar. These structures are usually formed by partially viable tissue, called Border Zone (BZ). Understanding the anatomical and electrical properties of the BZ is crucial to guide ablation therapy to the right targets, reducing the likelihood of VT recurrence. Virtual Heart methods can provide ablation guidance non-invasively, but they have high computational complexity and have shown limited capability to accurately reproduce the specific mechanisms responsible for clinically observed VT. These outstanding challenges undermine the utility of Virtual Hearts for high precision ablation guidance in clinical practice. In this work, fast phenomenological models are developed to efficiently and accurately simulate the re-entrant dynamics of VT as observed in 12-lead ECG. Two porcine models of Myocardial Infarction (MI) are used to generate personalized bi-ventricular models from pre-operative LGE-MRI images. Myocardial conductivity and action potential duration are estimated using sinus rhythm ECG measurements. Multiple hypotheses for the BZ tissue properties are tested, and optimal values are identified. These allow the Virtual Heart model to produce VTs with good agreements with measurements in terms of ECG lead polarity and VT cycle length. Efficient GPU implementation of the cardiac electrophysiology model allows computation of sustained monomorphic VT in times compatible with the clinical workflow.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Cardiac modeling; ECG simulation; VAAT; VT